Project-Based Learning as a Strategy to Improve Students’ Creativity in Elementary Social Studies - Basri, Rizki Isnaini; Elpisah Elpisah; W, Muh. Fahreza (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
This study aims to analyze the application of the Project-Based Learning (PjBL) model to improve students’ creativity in Social Studies and to measure its effectiveness in enhancing creative learning outcomes. The research was conducted as a Classroom Action Research (CAR) across two cycles during the even semester of the 2024/2025 academic year, involving 30 fifth-grade students at SD Inpres Barombong 2. Data were collected through observation, questionnaires, and documentation, while analysis employed descriptive statistics for quantitative data and reduction–triangulation techniques for qualitative data. The creativity indicators examined included fluency, flexibility, originality, and elaboration. Findings reveal that the implementation of PjBL significantly enhanced students’ creative thinking skills, as evidenced by an overall increase in average scores across all creativity indicators. Furthermore, the effectiveness of the PjBL model was reflected in the improved implementation of its instructional syntax, progressing from the “Moderate” category in the initial cycle to “High” and eventually “Very High” in the subsequent cycle. These outcomes confirm that PjBL promotes active, student-centered, and collaborative learning that fosters creativity in Social Studies. The study concludes that continuous implementation of PjBL is essential for cultivating creativity in elementary classrooms and suggests further research to explore its applicability in different contexts and educational levels.